The 'Flypaper Effect' in Presence of Spatial Interdependence : Evidence from Argentinean Municipalities - Acosta, Pablo (2012)
The "flypaper effect", when an unconditional lump-sum grant to a local government increases spending in a greater proportion than an equivalent raise in local income, has been extensively documented in the literature. This paper shows new estimates in the presence of spatial dependence, when local spending is not independent from its neighbor jurisdictions' behavior. Using county-level data for Buenos Aires (Argentina), this study shows that while the "flypaper effect" still holds true in the presence of spillover effects or mimic behavior across jurisdictions, it could be overestimated in the presence of spatial interdependence.